Osteogenic differentiation and proliferation of apical papilla stem cells using nanoparticles of Neo MTA and bioactive glass - H. Abdelaziz; Abeer H. Mahran; T. Elsewify (Elsevier, 2024)
Objective: The aim of this study was to evaluate the osteogenic differentiation ability and proliferation of apical papilla stem cells using nanoparticles of Neo MTA and bioactive glass. Methods: Neo MTA and bioactive glass 45S5 nanoparticles were prepared and characterized using a transmission electron microscope and X-ray diffraction. Apical papilla stem cells were harvested from freshly-extracted fully-impacted wisdom teeth, cultured, and characterized using flow cytometric analysis. Tested nanomaterials were mixed and samples were classified into four equal groups as follows; Negative control group: SCAP with Dulbecco's modified eagle's medium, Positive control group: SCAP with inductive media, First experimental group: Neo MTA nanoparticles with SCAP, Second experimental group: Bioactive glass nanoparticles with SCAP. Osteoblastic differentiation was assessed using an alkaline phosphatase assay and RANKL expression using specific polyclonal antibodies by fluorescence microscope. The proliferation of SCAP was assessed using cell count and viability of Trypan Blue in addition to an MTT assay. Results: Isolated SCAP showed a non-hematopoietic origin. Neo MTA showed the highest ALP concentration followed by bioactive glass nanoparticles, and negative control. Bioactive glass nanoparticles showed the highest H score for RANKL protein expression followed by Neo MTA, and negative control. Bioactive glass nanoparticles showed the highest viable cell count. Conclusions: SCAP isolation is achievable from extracted fully impacted immature third molars. Both tested nanobiomaterials have the ability to induce osteogenic differentiation and proliferation of SCAP.